Can Nesfatin-1 Predict Hypertension in Obese Children? - Hatice Güneş; Filiz Alkan Baylan; Hakan Güneş; Fatih Temiz (Galenos Yayincilik, 2020)
Objective:The prevalence of childhood obesity is increasing and leads to co-morbidities such as hypertension. However, it is still not clear why some obese individuals are hypertensive and others not. Nesfatin-1 is a recently discovered anorexigenic peptide which also has effects on blood pressure (BP). Our aim was to evaluate the relationship between obesity-related hypertension and Nesfatin-1.Methods:This cross-sectional study comprised 87 obese children. The patients were divided into two groups; hypertensive (n=30) and normotensive (n=57) obese. The American Academy of Pediatrics guidelines were used to diagnose hypertension. Blood samples were collected after 12 hours of fasting to investigate Nesfatin-1 concentrations. We also evaluated serum trace elements in addition to the routine blood tests.Results:Body mass index (BMI), weight and serum Nesfatin-1 concentrations were higher in the hypertensive group (p=0.002, p=0.001, and p=0.007, respectively). There was no difference between serum zinc levels, but Copper (Cu) levels were significantly lower in the hypertensive group (p=0.248, p=0.007, respectively). There were positive correlations between BP and BMI and weight Z-scores and a negative correlation with Cu. The optimal cut-off value of Nesfatin-1 to predict hypertension was found to be >1.8 ng/mL, with a specificity of 71.9% and a sensitivity of 96.7% [area under the curve=0.703, 95% confidence interval (CI): 0.577-0.809; p=0.002]. In multiple logistic regression analysis Nesfatin-1 [Odds ratio (OR)=1.103, 95% CI: 1.039-1.171; p=0.001], Cu (OR=0.947, 95% CI: 0.915-0.979; p=0.001) and BMI for age Z-score (OR=56.277, 95% CI: 5.791-546.907; p=0.001) still remained significant predictors of hypertension.Conclusion:Nesfatin-1 levels are higher and are an independent predictor of hypertension in obese subjects.